Pelatihan pembuatan Minyak Kelapa Murni (Virgin coconut oil) Menggunakan Metode Endapan/Pendiaman Di Kelompok Tani Efata Desa Sunsea Kecamatan Naibenu Kabupaten Timor Tengah Utara: Pelatihan pembuatan Minyak Kelapa Murni (Virgin coconut oil) Menggunakan Metode Endapan/Pendiaman Di Kelompok Tani Efata Desa Sunsea Kecamatan Naibenu Kabupaten Timor Tengah Utara - Kolo, Maria Magdalena; Batu, Matius Stafenus (Bakti Cendana, 2023)
The Efata Farmers Group is a farmer group located in Sunsea Village, Naibenu District, North Central Timor Regency, whose daily activities are farming and raising livestock. Sunsea Village has coconut trees which produce coconuts in large quantities and are only used to make coconut oil by heating for cooking purposes. Even though coconut can produce pure oil or commonly called Virgin Coconut Oil (VCO). The purpose of this community service activity is to train members of the Sunsea Village Efata Farmer Group to produce quality Virgin Coconut Oil (VCO) oil products using a simple method. The activity implementation method uses focus group discussion (FGD). The activities carried out included training in VCO production using the settling/dwelling method, organoleptic testing of VCO quality and assessing the knowledge and understanding of partner groups. It was concluded that the partner group was very enthusiastic about participating in the activity as seen from attendance (100%). The stages of making VCO have been carried out and produced quality VCO from an organoleptic point of view, such as being clear in color and having a distinctive coconut smell. The partner group also experienced an increase in understanding and knowledge about VCO from 35% to 92.5%.